The origin and nature of life on Earth : the emergence of the fourth geosphere - Smith, Eric (Cambridge University Press, 2016)
"Uniting the conceptual foundations of the physical sciences and biology, this ground-breaking multi-disciplinary book explores the origin of life as a planetary process. Combining geology, geochemistry, biochemistry, microbiology, evolution and statistical physics to create an inclusive picture of the living state, the authors develop the argument that the emergence of life was a necessary cascade of non-equilibrium phase transitions that opened new channels for chemical energy flow on Earth"--